1986
DOI: 10.1111/j.1440-1681.1986.tb00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Renal Function in the Rat Remnant Kidney Model of Chronic Renal Failure by Blood Pressure Reduction

Abstract: The remnant kidney model of chronic renal failure was established in female Sprague-Dawley rats subjected to surgical removal of the right kidney and segmental infarction of seven-eighths of the left kidney. Plasma creatinine (mumol/l) rose from 65 (s.e.m. = 16, n = 18) to 153 (s.e.m. = 27, t-test, P less than 0.001, d.f. = 17) over 6 weeks. Histological glomerulosclerotic lesions were present from 2 weeks and prominent by 6 weeks post-surgery. Rats were treated with enalapril (5 mg/kg per day, n = 11) or felo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…These effects on the remnant kidney function in this model of rats following blood pressure reduction by calcium channel blockers are consistent with the previous reports (Jackson et al 1986; Jackson and Johnston 1988). Treatment of hypertension with indapamide, possessing both natriuretic and direct vasodilatory activity (Van Zwieten 1984), or the calcium channel blocker benidipine, produced a milder and comparable decrease in blood pressure, but had dissimilar effects on renal function in SHR with reduced renal mass.…”
Section: Discussionsupporting
confidence: 81%
“…These effects on the remnant kidney function in this model of rats following blood pressure reduction by calcium channel blockers are consistent with the previous reports (Jackson et al 1986; Jackson and Johnston 1988). Treatment of hypertension with indapamide, possessing both natriuretic and direct vasodilatory activity (Van Zwieten 1984), or the calcium channel blocker benidipine, produced a milder and comparable decrease in blood pressure, but had dissimilar effects on renal function in SHR with reduced renal mass.…”
Section: Discussionsupporting
confidence: 81%
“…Eliahou et al [15] administered nisoldipine starting immediately after renal ablation, which prevented hypertension, had little effect on proteinuria, but improved survival in male and female Charles River rats. These reports of beneficial effects of calcium antagonists are at variance with studies in remnant-kidney rats performed earlier in our laboratory [1] and by Jackson et al [13]. The latter authors reported a tendency to increased proteinuria in female Sprague-Dawley rats despite excellent control of hypertension after 6 weeks of treatment with the calcium channel blocker felodipine.…”
Section: Introductioncontrasting
confidence: 56%
“…However, in the most extensively studied model of chronic renal failure, the remnantkidney rat, the response to different antihypertensive regimens is not uniform. Control of hypertension by ACE inhibitors has proven to be superior to triple-drug therapy with hydralazine, reserpine, and hydrochlorothiazide regarding prevention or delay in progressive glomerulosclerosis [12], and the highly protective effect of ACE inhibitors was invariably associated with greatly reduced proteinuria [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These results can be ascribed, to a great extent, to the lower SBP observed in MNF rats up to 6 wk of observation ( Table 1). The importance of reducing blood pressure to slow the progression of CRF, in fact, is widely recognized in many experimental and clinical studies, with the best results obtained with angiotensin-converting enzyme inhibitors, which increase the availability of NO (13,14,17,20). All of these studies have clearly demonstrated the direct correlation between the levels of SBP and both the functional and histological damage in the kidney; this study further strengthens how lower levels of SBP may positively influence the course of CRF, mostly when associated to a greater availability of NO, as in the case of MNF rats.…”
Section: Discussionmentioning
confidence: 99%